Education-related Inequity in Health Care with Heterogeneous Reporting of Health - Teresa Bago d'Uva; Maarten Lindeboom; Owen O'Donnell; Eddy van Doorslaer (Tinbergen Institute, 2010)
Reliance on self-rated health to proxy medical need can bias estimation of education-related inequity in health care utilisation. We correct this bias both by instrumenting self-rated health with objective health indicators and by purging self-rated health of reporting heterogeneity identified from health vignettes. Using data on elderly Europeans, we find that instrumenting self-rated health shifts the distribution of doctor visits in the direction of inequality favouring the better educated. There is a further, and typically larger, shift the same direction when correction is made for the tendency of the better educated to rate their health more negatively.
Keywords: C35; C42; I12; 330; health care; health; equity; reporting heterogeneity; vignettes; Gesundheitsversorgung; Alte Menschen; Soziale Ungleichheit; Bildungsniveau; Europa